1978
DOI: 10.1152/ajpendo.1978.234.1.e79
|View full text |Cite
|
Sign up to set email alerts
|

Salivary gland K+ transport: in vivo studies with K+-specific microelectrodes.

Abstract: Stimulation-induced transport of K+ in the submandibular salivary gland of cats and dogs anesthetized with pentobarbital was studied with an extracellular K+-specific microelectrode. Electrical stimulation of the para-sympathetic chorda-lingual nerve caused a rapid transient increase in extracellular K+ concentration from 2.2 to 18.7 meq/liter in the cat and from 2.3 to 15.2 meq/liter in the dog. Eventually the K+ concentration fell below the prestimulatory level, indicating uptake of K+ by the gland cells. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
7
0

Year Published

1978
1978
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 10 publications
6
7
0
Order By: Relevance
“…The time course of the net K movement induced by ACh, a-adrenergic agonists and substance P in the present experiments resembles that induced by prolonged parasympathetic stimulation in the perfused cat and dog submaxillary glands in 8itU (Poulsen & Bledsoe, 1978), since the K release induced by agonists was transient and fell to the pre-stimulation level during stimulation ( Fig. 2A, B and D).…”
Section: Discussionsupporting
confidence: 71%
“…The time course of the net K movement induced by ACh, a-adrenergic agonists and substance P in the present experiments resembles that induced by prolonged parasympathetic stimulation in the perfused cat and dog submaxillary glands in 8itU (Poulsen & Bledsoe, 1978), since the K release induced by agonists was transient and fell to the pre-stimulation level during stimulation ( Fig. 2A, B and D).…”
Section: Discussionsupporting
confidence: 71%
“…If this were the case in the present study, then the initial potential change of the parotid cells could be explained by increased K + efflux, with EAC h equal to E~. However, it is unlikely that K § accumulated in our tissue segments to the same extent as reported by Poulsen and Bledsoe (1977) in vivo since Petersen, Gray and Hall (1977) have shown that in the superfused parotid, the rapid flow of bathing fluid prevented any marked rise in [K +] in the bath effluent. As our recordings were obtained from superficial cells it is likely that K § released from the cells was rapidly removed.…”
Section: Discussionsupporting
confidence: 59%
“…Previous reports have described increased sodium and potassium permeability in submandibular gland acinar cells stimulated with acetylcholine (Petersen, 1970(Petersen, , 1972Nishiyama & Petersen, 1974a;Poulsen, 1974). Recently Poulsen and Bledsoe (1977) have demonstrated that the concentration of K § in the interstitial fluid of cat and dog submandibular glands could rise to as high as 18 ms during the period of parasympathetic nerve stimulation. If this were the case in the present study, then the initial potential change of the parotid cells could be explained by increased K + efflux, with EAC h equal to E~.…”
Section: Discussionmentioning
confidence: 92%
“…Cook and colleagues (5, 6) hypothesized that fluid secretion can be driven by K channels in the apical membrane of acinar cells. In fact, there is direct evidence for an apical maxi-K-like current in the acinar cells of frog skin (41) and for apical Ca 2ϩ -activated K ϩ currents in rat lacrimal acinar cells (44 (30,50). Because the K ϩ and Na ϩ concentrations of both the acinar secretions and the venous plasma outflow from salivary gland (which reflects the interstitial ion concentration) are plasma-like, this suggests that K ϩ and Na ϩ likely enter the primary saliva across the "leaky" tight junctions of the acinus.…”
Section: Discussionmentioning
confidence: 99%